Impact of chronic respiratory symptoms in a rural area of sub-Saharan Africa: an in-depth qualitative study in the Masindi district of Uganda - van Gemert, Frederik (Prim Care Respir J, 2013)
BACKGROUND: Chronic obstructive pulmonary disease (COPD), once regarded as a disease of developed countries, is now recognised as a common disease in low- and middle-income countries. No studies have been performed to examine how the community in resource-poor settings of a rural area in sub-Saharan Africa lives with chronic respiratory symptoms. AIMS: To explore beliefs and attitudes concerning health (particularly respiratory illnesses), use of biomass fuels, tobacco smoking, and the use of health services. METHODS: A qualitative study was undertaken in a rural area of Masindi district in Uganda, using focus group discussions with 10–15 members of the community in 10 randomly selected villages. RESULTS: Respiratory symptoms were common among men, women, and children. In several communities respiratory symptoms were stigmatised and often associated with tuberculosis. Almost all the households used firewood for cooking and the majority cooked indoors without any ventilation. The extent of exposure to tobacco and biomass fuel smoke was largely determined by their cultural tradition and gender, tribal origin and socioeconomic factors. Many people were unaware of the damage to respiratory health caused by these risk factors, notably the disproportionate effect of biomass smoke in women and children. CONCLUSIONS: The knowledge of chronic respiratory diseases, particularly COPD, is poor in the rural community in sub-Saharan Africa. The lack of knowledge has created different beliefs and attitudes concerning respiratory symptoms. Few people are aware of the relation between smoke and respiratory health, leading to extensive exposure to mostly biomass-related smoke.